Structure–Function Analysis Reveals Amino Acid Residues of Arabidopsis Phosphate Transporter AtPHT1;1 Crucial for Its Activity - Liao, Ya-Yun; Li, Jia-Ling; Pan, Rong-Long; Chiou, Tzyy-Jen (Frontiers in Plant Science, 2019)
Phosphorus (P), an essential plant macronutrient, is acquired in the form of inorganic phosphate (Pi) by transporters located at the plasma membrane of root cells. To decipher the Pi transport mechanism, Arabidopsis thaliana Pi transporter 1;1 (AtPHT1;1), the most predominantly H+-coupled Pi co-transporter in the root, was selected for structure–function analysis. We first predicted its secondary and tertiary structures on the basis of the Piriformospora indica Pi transporter (PiPT) and identified 28 amino acid residues potentially engaged in the activity of AtPHT1;1. We then mutagenized these residues into alanine and expressed them in the yeast pam2 mutant defective in high-affinity Pi transporters and Arabidopsis pht1;1 mutant, respectively, for functional complementation validation. We further incorporated the functional characterization and structure analyses to propose a mechanistic model for the function of AtPHT1;1. We showed that D35, D38, R134, and D144, implicated in H+ transfer across the membrane, and Y312 and N421, involved in initial interaction and translocation of Pi, are all essential for its transport activity. When Pi enters the binding pocket, the two aromatic moieties of Y145 and F169 and the hydrogen bonds generated from Q172, W304, Y312, D308, and K449 can build a scaffold to stabilize the structure. Subsequent interaction between Pi and the positive residue of K449 facilitates its release. Furthermore, D38, D93, R134, D144, D212, R216, R233, D367, K373, and E504 may form internal electrostatic interactions for structure ensemble and adaptability. This study offers a comprehensive model for elucidating the transport mechanism of a plant Pi transporter.